Aproximações teóricas entre a praxiologia motriz e a proposta transformação didático-pedagógica do esporte: por um diálogo da possibilidade - Taborda, Douglas dos Santos (2014)
Introduction: This study accomplished a theoretical-conceptual approach between Motor Praxeology and Proposal Didactic and Pedagogical Transformation of Sport (TDPE). The objectives were: a) Theoretical Review about motor praxeology; b) Theoretical Review about TDPE ; c) Praxeological Review on the criteria used for the preparation of tasks of teaching and learning cooperation/opposition sports TDPE included in the proposal; and d) the development of educational-learning examples approaching knowledge of motive praxiology with the pedagogical assumptions of the TDPE Proposal. Methodology: It was characterized by a theoretical research (DEMO 2000) since it allowed to analyze, to reflect, to organize and to rebuild didactic and pedagogical knowledge. Results: The analyzes allowed to discuss / reflect on didactic-methodological alternatives for teaching opposition/cooperation sports in a school context, guided by the theories /proposals here analyzed. Conclusions: This study allowed emphasizing the relevance of praxeological knowledge as theoretical-pedagogical instrumentalization to the physical education teacher, as well as demonstrated how motor praxeology can dialogue with the Sport Didactic and Pedagogical Transformation Proposal.